Functionality of Patients 75 Years and Older Undergoing Mohs Micrographic Surgery: A Multicenter Study. Issue 7 (July 2017) - Regula, Christie G.; Alam, Murad; Behshad, Ramona; Glashofer, Marc; Hanke, C. William; Harmon, Christopher; Johnson, Ryan; Kent, David; Lee, Patrick; Lawrence, Naomi
Abstract : BACKGROUND: Mohs surgery is indisputably a highly effective treatment for nonmelanoma skin cancers. In the current health care environment, physicians are challenged to provide high quality, efficacious care in a manner that is mindful of the patient's general health and well-being. We have used a functional assessment to evaluate older patients who present for Mohs surgery. OBJECTIVE: The purpose of this study is to categorize the functional status, using the Karnofsky Performance Status (KPS) Scale, of patients 75 years and older undergoing Mohs surgery of a nonmelanoma skin cancer and to identify distinguishing characteristics of lower functioning patients. METHODS: Patients 75 years and older undergoing Mohs surgery for nonmelanoma skin cancer at 8 separate geographically diverse sites were included. Patient and tumor characteristics were recorded. Physicians scored subjects on the KPS scale and administered a questionnaire to categorize the symptoms and impact of their skin cancer. RESULTS: A total of 291 subjects completed the study. The average KPS score was 90.1. 93.1% of our subjects had a KPS score of ≥70. Subjects with a KPS score <70 were more likely to be older with larger symptomatic tumors. CONCLUSION: The vast majority of patients 75 years and older undergoing Mohs surgery are highly functioning. Lower functioning patients are older with larger symptomatic tumors that negatively impact their lives.